Comprehensive insights into language education : A compilation from ICoLLT 2024 - Abdullah Adnan, Mohamed; Asiah, Kassim; Azwin Arif, Abdul Rahim; Wu, Chunlian; Ezihaslinda, Ngah; Guo, Lichao; Hafizoah, Kassim; Mukhtar, Hafsa Pir; Ali, Imanat; Li, Changlin; Mohammad Musab, Azmat Ali; Mohd Amir Izuddin, Mohamad Ghazali; et al. (Universiti Malaysia Pahang Al-Sultan Abdullah, 2025)
Language education is constantly evolving, and Comprehensive Insights into Language Education : A Compilation from ICoLLT 2024 offers educators, reseachers, and policymakers an invaluable resource to engage with this dynamic field. This book brings together cutting-edge research and innovative practices shared during the International Conference on Language Learning and Teaching 2024, providing practical strategies to address modern challenges in teaching and learning.